EVALUATION OF APOA VERSION 2.0 SOCIALIZATION ACTIVITIES TO IMPROVE THE CADRE OF SUPERVISION OF FOREIGNERS IN SOUTH SULAWESI - Kiki Ananda Mustari; Rahmawati Nurul Jannah (Polteknik Imigrasi, 2021)
The purpose of this socialization activity is to provide information about the Foreigner Monitoring Application (APOA). The presence of foreigners who enter South Sulawesi through domestic arrivals makes these foreigners not included in the list of foreigners in South Sulawesi because they do not go through immigration checks. This results in less accurate data on foreigners and supervision of foreigners. The lack of data for foreigners has resulted in the vulnerability of foreign nationals to commit administrative criminal offenses such as overstaying and working without a valid permit. With the existence of APOA, it will make it easier for the PORA TEAM to carry out surveillance of foreigners in South Sulawesi in collaboration with the owners/managers of the inn and community leaders.